Ash dieback due to Hymenoscyphus fraxineus: what can be learnt from evolutionary ecology?. (11th May 2016) - Landolt, J.; Gross, A.; Holdenrieder, O.; Pautasso, M.
Abstract : The future existence of common ash ( Fraxinus excelsior ), an important tree species throughout temperate Europe, is threatened. An invasive fungal disease (ash dieback) has spread through much of the distribution area of common ash. The causal agent of the disease is Hymenoscyphus fraxineus, a necrotrophic ascomycete, most probably introduced from Asia in the early 1990s. Hymenoscyphus fraxineus infects ash trees and saplings through their leaves, from which it grows into the stem. The fungus was studied intensively in recent years but there is still a need to address the topic from an evolutionary perspective. In this overview, some key evolutionary aspects of ash dieback are discussed, from the Red Queen dynamics of host–pathogen interactions to the probable consequences for virulence evolution of multiple infections. The progression of ash dieback in Europe does not show spatial differences, but studies show variation in susceptibility within host populations, a probable consequence of genetic differences, thus providing material for evolution of disease resistance or tolerance. Breeding programmes need to maintain the genetic diversity of Fraxinus, to enable it to withstand further threats such as climate change and the emerald ash borer. Because H. fraxineus reproduces exclusively sexually, the pathogen is likely to overcome a narrow genetic resistance. The introduction of further strains of H. fraxineus to Europe and the movement of infected plant material should be avoided. This case study shows that the integration of evolutionary ecology considerations would benefit plant disease management and biosecurity in general.